Acetylcholinesterase 1 in populations of organophosphate-resistant North American strains of the cattle tick, Rhipicephalus microplus (Acari: Ixodidae) - Bendele, K.; Guerrero, F.; Miller, R.; Li, A.; Barrero, R.; Moolhuijzen, Paula; Black, M.; McCooke, J.; Meyer, J.; Hill, C.; Bellgard, M. (Springer Verlag, 2015)
Rhipicephalus microplus, the cattle fever tick, is a global economic problem to the cattle industry due to direct infestation of cattle and pathogens transmitted during feeding. Cattle fever tick outbreaks continue to occur along the Mexico-US border even though the tick has been eradicated from the USA. The organophosphate (OP) coumaphos targets acetylcholinesterase (AChE) and is the approved acaricide for eradicating cattle fever tick outbreaks. There is evidence for coumaphos resistance developing in cattle ticks in Mexico, and OP-resistant R. microplus ticks were discovered in outbreak populations of Texas in 2005. The molecular basis of coumaphos resistance is not known, and our study was established to gather further information on whether AChE1 is involved in the resistance mechanism. We also sought information on allele diversity in tick populations with different levels of coumaphos resistance. The overarching project goal was to define OP resistance-associated gene mutations such that a DNA-based diagnostic assay could be developed to assist the management of resistance. Three different AChE transcripts have been reported in R. microplus, and supporting genomic and transcriptomic data are available at CattleTickBase. Here, we report the complete R. microplus AChE1 gene ascertained by sequencing a bacterial artificial chromosome clone containing the entire coding region and the flanking 5' and 3' regions. We also report AChE1 sequences of larval ticks from R. microplus strains having different sensitivities to OP. To accomplish this, we sequenced a 669-bp region of the AChE1 gene corresponding to a 223 amino acid region of exon 2 to assess alleles in seven strains of R. microplus with varying OP resistance phenotypes. We identified 72 AChE1 sequence variants, 2 of which are strongly associated with OP-resistant phenotypes. Esterase-like sequences from the R. microplus transcriptome RmiTr Version 1.0 were compared to the available sequence databases to identify other transcripts with similarity to AChE1.